2008
DOI: 10.1080/17461390802020868
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Spanish adolescents’ physical activity patterns by seasonality, day of the week and demographic factors

Abstract: In this study, we examined the variability of physical activity (and inactivity) patterns in relation to gender, age, type of school, day of the week, and season of the year among a sample of Spanish adolescents aged 12Á16 years. Levels of physical activity engagement, ''who'' was active/inactive, and ''when'' they were active/inactive were addressed. A Spanish translation and modification of Cale's Four by One-Day Physical Activity Questionnaire was administered by interviewer to 323 participants to measure e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
25
3
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 30 publications
7
25
3
2
Order By: Relevance
“…In addition, males participated in both moderate and vigorous activities for longer periods of time than females. These findings are in line with the earlier studies which found that boys were physically more active than girls (Katzmarzyk et al, 1999;Lasheras et al, 2001;McKenzie et al, 2000;Pahkala et al, 2007;Peiro-Velert et al, 2008), and also that males were more active than females (Grundy et al, 1999;Johnson et al, 1998;Kronenberg et al, 2000;Lowry et al, 2002;Macera et al, 2001;Moore et al, 2005;Trost et al, 2002;Utter et al, 2006). Moreover, the results of the present study revealed that males were more likely than females to play team sports such as soccer and basketball, while female participation was concentrated on individual exercise and sport activities such as walking and table-tennis.…”
Section: Discussionsupporting
confidence: 83%
“…In addition, males participated in both moderate and vigorous activities for longer periods of time than females. These findings are in line with the earlier studies which found that boys were physically more active than girls (Katzmarzyk et al, 1999;Lasheras et al, 2001;McKenzie et al, 2000;Pahkala et al, 2007;Peiro-Velert et al, 2008), and also that males were more active than females (Grundy et al, 1999;Johnson et al, 1998;Kronenberg et al, 2000;Lowry et al, 2002;Macera et al, 2001;Moore et al, 2005;Trost et al, 2002;Utter et al, 2006). Moreover, the results of the present study revealed that males were more likely than females to play team sports such as soccer and basketball, while female participation was concentrated on individual exercise and sport activities such as walking and table-tennis.…”
Section: Discussionsupporting
confidence: 83%
“…This "high weekdays-low weekends" PA pat terns were already examined in previous studies in adults (Tudor-Locke et al, 2004), adolescents (Peiró-Velert et al, 2008;Pelclová, Ansari, & Vašíčková, 2010) and as well as in children (Duncan et al, 2008a). This study contributes to these fi ndings by recognizing that these patterns are similar in girls regardless of their frequency of participation in organised PA.…”
Section: Discussionmentioning
confidence: 99%
“…Differences between boys and girls have been minimally affected by this. We did not study other factors that may influence performing physical activities for example weather conditions (Duncan, Hopkins, Schofield, & Duncan, 2008;Suminksi, Poston, Market, Hyder, & Sara, 2008), season (Pieró-Veler, Devís-Devís, Beltrán-Carrillo, & Fox, 2008), and environment (Davison & Lawson, 2006;Ding, Sallis, Kerr, Lee, & Rosenberg, 2011;Nelson, Gordon-Larsen, Song, & Popkin, 2006).…”
Section: Strengths and Limits Of The Studymentioning
confidence: 99%